CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IN THE CONTEXT OF THE SHARING ECONOMY: CHALLENGES AND OPPORTUNITIES - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Customer Relationship Management (CRM) plays an important role in the sharing economy ecosystem, where trust and customer relationships are key success factors. This research explores the opportunities and challenges that arise from CRM implementation in the context of the sharing economy. In terms of opportunities, CRM enables companies to build more personalised and in-depth relationships with customers, improve operational efficiency through automation, and leverage data to increase customer satisfaction and loyalty. On the other hand, challenges include customer data privacy concerns, the need for high security, and adaptation to fast-changing market dynamics. Nonetheless, if managed well, CRM implementation can add significant value in creating superior customer experiences and supporting sustainable business growth in the sharing economy.